Influence of Urban Rail Transit Lines Turn-back Forms and Influencing Factors on the Turn-back Capacity - ZENG Xiao’er (Chengshi guidao jiaotong yanjiu)
［Objective］ Improving the turn-back capacity, a key indicator for evaluating the transportation efficiency of urban rail transit lines, is an important issue currently being faced. Therefore, it is of particular importance to conduct an in-depth analysis of the influence of urban rail transit turn-back forms and the related factors on turn-back capacity. ［Method］ In the case study of an actual operating urban rail transit line, a set of urban rail transit train operation simulation systems independently developed by the laboratory is adopted to calculate and analyze the turn-back capacity under various turn-back forms. According to the detailed process of turn-back operations, various factors affecting the turn-back interval are qualitatively analyzed, and the influence of the related factors on the turn-back capacity is studied. On this basis, optimization measures are put forward and quantitatively verified in specific types of station. The improvement capabilities and limiting conditions of each optimization measure are calculated under different turn-back forms. ［Result & Conclusion］ Under normal circumstances, the turn-back capacity of the train turning back behind the station is stronger than that in front of the station. The proposed optimization measures such as shortening the stop time, increasing the turnout lateral speed limit, lowering the requirements for train control comfort and parking accuracy, and shortening the train end-switching time have different improvement effects under different turn-back forms, and need to be flexibly selected according to the actual situation. The turn-back capacity is significantly improved with the train turn-back form based on vehicle-to-vehicle communication compared with the traditional one based on vehicle-to-ground communication.